Emerging Role of E-Wallets in Increasing Financial Inclusion in India - Beg, Sana; Shafeeq, Mohd. (Gyan Management Journal, 2018)
The journey of India towards achieving complete financial inclusion is still a challenge. The road to  financial inclusion that we are following will someday lead us to it, but how long will it1take no one  knows mainly because of the geographical spread of our country. Ever since independence,  governments and agencies have been continuously working towards increasing financial inclusion.  This paper is an attempt to assess the emerging role of e-wallets in financial inclusion in India. E-wallet  can be a boon for financial inclusion, as it has no geographical limits. This paper focuses on studying the  role of e-wallet and ATMs in increasing financial inclusion. In the last few years, there has been an  inconsistent growth of ATMs in India (increasing in one month, decreasing in the other). It is possible  that this inconsistent growth of ATMs could possibly be because of demonetization. However, to be  noted is that because of demonetization in the country people started using e-wallets in a big way and  thus e-wallets can give great push towards achieving financial inclusion.
Keywords: Financial Inclusion; Technology; E-wallet; Mobile Financial Services andATMs